Validação de método para determinação de desoxinivalenol e sua influência na qualidade tecnológica da farinha de trigo - Gai , Daniela Stefani Honnef (2018)
Wheat is used in the food industry because of its functional, technological and nutritional properties. Contamination of grain by fungi results in a decrease in commercial quality, which harms both the producer and the food industry. The mycotoxin with the highest incidence in wheat is deoxynivalenol caused by the fungus of the Fusarium species, which, even in low concentrations, can be toxic to those who consume it besides devaluing the grain next to the market. In order to minimize the presence of this contaminant in the grain, the agriculture has used fungicides seeking the satisfactory control of the fungus. The objective of this work was to evaluate the incidence of mycotoxin deoxynivalenol in wheat submitted to fungicide application and the technological quality of this product for baking. In order to determine the mycotoxin deoxynivalenol and the fungicides carbendazin, tebuconazole, metconazole, mancozeb and pyraclostrobin in wheat grains, an analytical method was validated that showed low detection limits and high sensitivity, based on the QuEChERS method, widely used in multiresistant analysis, and determination LC MS / MS. The technological quality of the wheat was evaluated through physicochemical and rheological analyzes in whole grain wheat flour. The significance of the data was performed by the Skott-Knott test with error probability of 5%. The samples showed different levels of contamination by DON, but the results indicated that the fungicides have control under the contamination of the mycotoxin, without leaving residues in the final product. The results of the physico-chemical characterization of the FTGI the T1-control sample differed significantly in relation to the protein content of the other samples, this is believed to have occurred due to the formation of fungal protein. In the rheological analysis, the T9 sample presented a significant difference in comparison to the other samples in the parameters of mass stability and wet gluten, but it was verified that there is no direct relation of these parameters with the contamination by the mycotoxin deoxynivalenol, since the control has the higher values of contamination and obtained good results in these analyzes. Samples T2, T10 and T11 and T12 showed a significant difference in the maximum viscosity parameter in the RVA analysis, when compared to the others, but in samples T11 and T12 the concentration of mycotoxin DON is higher than in samples T2 and T10, or The results of theregression parameter follow the same trend as those found in the parameter of maximum viscosity and final viscosity, the samples T11 and T12 had a significant difference and in comparison with the different levels of deoxynivalenol found, the concentration of DON did not increase the retrogradation. Analyzing the results obtained in the analytical quantifications in comparison with the physical-chemical and rheological analyzes, it is concluded that the different levels of contamination obtained by the mycotoxin deoxynivalenol does not interfere in the technological quality of the final product